Breast Reconstruction (A method for Augmentation) - S. S. Sethi (Indian Journal of Plastic Surgery)
1. Da Silva markings of the breast have been described for performing Strombeck procedure for reduction mammaplasty, instead of Strom-beck's standard patterns.